NGHIÊN CỨU ĐẶC ĐIỂM SINH HỌC VÀ ĐA DẠNG DI TRUYỀN CỦA MỘT SỐ CHỦNG NẤM SÒ VUA PLEUROTUS ERYNGII - Nguyễn Thị Bích Thùy (Di truyền học và ứng dụng - Chuyên san Công nghệ sinh học, 2016)
The King Oyster mushroom strains was cultivated on agar medium. The experiment results indicated that the King Oyster mushroom mycelium grew best at 26 °C± 1. when the temperature is below 22 degrees, body fruit formation is appeared, body fruit formation of E1-E5 strains do not develop into mature body fruit, E6 strains develop into mature fruit. Studies of genetic diversity in six Pleurotus eryngii strains with 23 RAPD primers. Results obtained: The genetic similarity coefficient of the samples ranged from 0.64 to 0.85; coefficient of genetic similarity of E6 strain with other strains is low (0.64 to 0.68); two samples 3 and 4 have the highest similarity coefficient is 0.85.